Efektivitas Model Pembelajaran Contextual Teaching And Learning (Ctl) Dengan Menggunakan Alat Peraga Stantick Terhadap Kemampuan Pemecahan Masalah Matematika - Salsabila, Aulia Tsana; Mardhiyana , Dewi (Publikasi Indonesia, 2025)
This research was motivated by the low ability of students in solving mathematical problems, which is caused by the use of traditional teaching methods and the lack of utilization of instructional media. To address this issue, the study aims to implement the Contextual Teaching and Learning (CTL) model supported by STANTICK teaching aids as an alternative to improve the mathematical problem-solving skills of tenth-grade students at SMK Negeri 1 Kandeman. This research employs a quantitative approach with a posttest-only control group design. The sample was selected using the cluster random sampling technique, which involves randomly selecting samples from clusters. Out of six classes in the population, two were randomly chosen as the research sample, namely class X TE 2 as the experimental group and class X TE 3 as the control group. Data were collected through an essay test based on single data statistics material. The analysis in this study utilized t-tests and proportion tests. The results revealed that the implementation of the CTL model assisted by STANTICK had a significant effect on students' mathematical problem-solving abilities compared to the conventional method. Moreover, the CTL learning model supported by STANTICK teaching aids enabled students to achieve mastery learning.